Editorial - Passing the Baton: 35 Years and Carrying On [Meneruskan Tongkat Estafet: 35 Tahun dan Terus Berjalan] - Ide Bagus Siaputra; Edwin Adrianta Surijah (Faculty of Psychology, Universitas Surabaya, 2019)
Editorial for ANIMA Indonesian Psychological Journal Volume 35, consisting of introduction and explanation regarding significant changes on ANIMA Indonesian Psychological Journal. Editorial untuk ANIMA Indonesian Psychological Journal Volume 35, berisi pendahuluan dan penjelasan atas perubahan penting di ANIMA Indonesian Psychological Journal.